2021
DOI: 10.1016/j.ejphar.2021.174082
|View full text |Cite
|
Sign up to set email alerts
|

Virtual high throughput screening: Potential inhibitors for SARS-CoV-2 PLPRO and 3CLPRO proteases

Abstract: The pandemic, COVID-19, has spread worldwide and affected millions of people. There is an urgent need, therefore, to find a proper treatment for the novel coronavirus, Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), the causative agent. This paper focuses on identifying inhibitors that target SARS-CoV-2 proteases, PL PRO and 3CL PRO , which control the duplication and manages the life cycle of SARS-CoV-2. We have carried out detailed in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…Indeed, there is a report showing that DSB partially inhibits the RdRp activity of Middle East respiratory syndrome coronavirus (MERS-CoV) ( 23 ). Targeting of viral protease might be another scenario for the inhibition; a very recent virtual screening study predicted that dasabuvir has the potential to inhibit 3-chymotrypsin-like protease (3CL PRO ) of SARS-CoV-2 ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, there is a report showing that DSB partially inhibits the RdRp activity of Middle East respiratory syndrome coronavirus (MERS-CoV) ( 23 ). Targeting of viral protease might be another scenario for the inhibition; a very recent virtual screening study predicted that dasabuvir has the potential to inhibit 3-chymotrypsin-like protease (3CL PRO ) of SARS-CoV-2 ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The main protease (Mpro) and the papain-like protease (PLpro) can be targets for anti-SARS-CoV-2 drugs. Research in this direction is prevalent and concerns mainly common natural compounds or repurposing of already used drugs [35][36][37][38]. Studies presented in this article are first concerning the activity of xanthophylls against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, His41 and Cys144 were the key amino acids that have catalytic activity in PEDV and TGEV 3CLpro and form the S1 pocket together with Phe139, Ile140, Gly142, Ala143, His162, Gln163, Glu165, and His171 [ 33 , 48 ]. Meanwhile, several studies reported that natural compounds in traditional herbs could bind to the 3CLpro of CoV, leading to the inhibition of viral replication [ 49 , 50 , 51 , 52 , 53 ]; in particular, the natural compound, quercetin, inhibited the PEDV 3CLpro through Cys144, Asn141, and His162 that were located in S1 [ 33 , 54 ]. In this study, we found the Asn141 and Glu165 in solution 2 ( Figure 3 and Figure S2 ) were part of this S1 pocket, indicating hypericin indirectly inhibit the catalytic activity of 3CLpro in PEDV.…”
Section: Discussionmentioning
confidence: 99%